Early Detection of Primary Open Angle Glaucoma by Using Optical Coherence Tomography - Kashif Ali, Abdul Majeed Malik, Saima Irum (Pakistan Journal of Ophthalmology, 2015)
Purpose: To measure and analyze thickness of retinal nerve fiber layer using Optical Coherence Tomography (OCT). Material and Methods: This study was conducted in ophthalmology department PNS Shifa, Karachi. From March 2013 to Jan 2015 for 23 months. A total of 350 glaucoma suspect patients were selected. A detailed history of ocular or systemic diseases was taken. Intraocular pressure (IOP) was measured using Goldmann Applanation tonometer. Optical Coherence Tomography (OCT) images were taken using Heidelberg HRA + OCT Spectralis machine. Results: Patients with a mean age of 35 ± 12 years were included. Out of 350 patients, 140 (40%) patients were female and 210 (60%) were male. Mean IOP was 25 ± 5 mm Hg, mode was 23 mm Hg and median 26 mm Hg. Out of these 350 suspects, only 28 patients were found to have nerve fiber layer thickness outside the normal limits i.e. decreased in half a quadrants or more. Conclusion: Ocular coherence tomography nerve fiber layer thickness analysis is a quick and effective method to diagnose early and borderline cases of glaucoma. Key Words: Optical coherence tomography (OCT), retinal nerve fiber layer (RNFL), glaucoma, intraocular pressure (IOP).